GAMPIL : Upaya Penguatan Daya Saing Ritel Mikro di Era COVID-19 dan Peningkatan Minat Memiliki Legalitas Usaha - Bob Foster; Muhamad Deni Johansyah (Jurnal Maps (Manajemen Perbankan Syariah), 2021)
In micro-scale retail, there are problems with the cost of legality management, the high costs and complicated rules are obstacles and the cause of the decrease in the number of legality ownership of micro-scale retailers. Based on this, the Bandung City Government, West Java, innovated using application technology and the internet for legality management, which was called the Gadget Application Mobile for License abbreviated as GAMPIL. This study is intended to determine whether efforts to strengthen internet-based applications can reduce the number of micro retailers that do not yet have legality and create a competitive power for micro-scale retailers in Indonesia, especially the city of Bandung. With a quantitative approach and explanatory research methods, 300 retailers from the city of Bandung, East Bandung to be exact, were taken randomly as a sample in the hope that the research can provide input for the government regarding strengthening the competitiveness of MSMEs in Bandung City through licensing. The results obtained are that the presence of GAMPIL as an application-based business license management innovation is able to increase the competitiveness of micro-scale retailers and their interest in having legality increases by 49.1%.